Cleavage of Syndecan-1 Promotes the Proliferation of the Basal-Like Breast Cancer Cell Line BT-549 Via Akt SUMOylation - Nadanaka, Satomi; Bai, Yaqiang; Kitagawa, Hiroshi (Frontiers in Cell and Developmental Biology, 2021)
Basal-like breast cancer is characterized by an aggressive clinical outcome and presence of metastasis, for which effective therapies are unavailable. We have previously shown that chondroitin 4-O-sulfotransferase-1 (C4ST-1) controls the invasive properties of the basal-like breast cancer cell line BT-549 by inducing matrix metalloproteinase (MMP) expression through the N-cadherin/-catenin pathway. Here we report that C4ST-1 controls the proliferation of BT-549 cells via the MMP-dependent cleavage of syndecan-1. Syndecan-1 is a membrane-bound proteoglycan associated with an aggressive phenotype and poor prognosis in breast cancer. In addition, the cleavage of syndecan-1 at a specific juxtamembrane cleavage site is implicated in the pathophysiological response in breast cancer. Knockout of C4ST-1 remarkably suppressed both the cleavage of syndecan-1 and proliferation of BT-549 cells. Kinases (AKT1, ERK1/2, PI3K, and STAT3) comprising cancer proliferative pathways are phosphorylated in C4ST-1 knockout cells at a level similar to that in parental BT-549 cells, whereas levels of phosphorylated S6 kinase and SUMOylated AKT (hyperactivated AKT observed in breast cancer) decreased in C4ST-1 knockout cells. An MMP inhibitor, GM6001, suppressed the small ubiquitin-like modifier (SUMO) modification of AKT, suggesting that cleavage of syndecan-1 by MMPs is involved in the SUMO modification of AKT. Forced expression of the cytoplasmic domain of syndecan-1, which is generated by MMP-dependent cleavage, increased the SUMO modification of AKT and global protein SUMOylation. Furthermore, syndecan-1 C-terminal domain-expressing BT-549 cells were more proliferative and sensitive to a potent SUMOylation inhibitor, tannic acid, compared with BT-549 cells transfected with an empty expression vector. These findings assign new functions to the C-terminal fragment of syndecan-1 generated by MMP-dependent proteolysis, thereby broadening our understanding of their physiological importance and implying that the therapeutic inhibition of syndecan-1 cleavage could affect the progression of basal-like breast cancer.